Phase change energy storage thermal insulation building material and preparation method thereof
By combining ethyl orthosilicate and polyvinylpyrrolidone in phase change energy storage materials to form porous silica, and paraffin is adsorbed into pores through vacuum adsorption, combining with the grafted dendritic polyamide amine, the The problem of easy oozing of the material during freeze-thawing process achieves the stability and anti-freeze properties of the material under high temperature and long-term freeze-thaw cycle.
Patent Information
- Application Number
- CN202411805711.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-10
- Publication Date
- 2025-02-14
AI Technical Summary
Existing phase change energy storage materials are prone to ooze out during freeze-thawing, affecting the stability and service life of the material.
Ethyl orthosilicate and polyvinylpyrrolidone are combined to form porous silica, and paraffin is completely adsorbed into the pores through vacuum adsorption. Combined with the grafted dendritic polyamide amine, paraffin is excellent in dispersion performance in the material. , and the freezing resistance of the material is enhanced by the ratio of the load phase change material to cement.
The stability and anti-freeze properties of phase-change energy storage materials under high temperature and long-term freeze-thaw cycles are achieved, and the service life of the materials is extended.
Smart Images

Figure CN119430772A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of building materials, and in particular to a phase-change energy storage thermal insulation building material and a preparation method thereof. Background Art
[0002] Phase change materials can store and release energy very well, and their own temperature remains almost unchanged during the whole process. Phase change materials refer to thermal functional materials that can absorb or release a large amount of surrounding heat energy by undergoing phase change while maintaining their own temperature unchanged when at their own phase change temperature. When the ambient temperature is higher than the phase change temperature of the phase change material, the material will absorb heat energy through phase change and store the absorbed heat energy in the material in the form of phase change latent heat; when the ambient temperature is higher than the phase change temperature of the phase change material, the material will release the absorbed phase change latent heat. At present, phase change materials are a type of thermal energy storage material with great application prospects. It can be used in many fields such as solar energy storage, energy-saving building materials and the preparation of temperature-regulating fibers.
[0003] With the rapid development of my country's economy and science and technology, energy consumption is increasing and becoming increasingly exhausted. Building energy consumption is an important aspect of energy consumption and waste. By rationally selecting building materials, such as building phase change energy storage materials, applying phase change energy storage technology to the construction field, and organically combining phase change materials and building materials to produce phase change energy storage building materials, the thermal insulation and heat storage capacity of the structure is enhanced, thereby reducing the indoor day and night temperature difference and improving indoor thermal comfort. It has a wide range of application prospects in actual engineering. At present, the research and development of phase change energy storage building materials has become one of the hot spots in the field of building energy conservation.
[0004] At present, by adding phase change materials into concrete to make phase change temperature controlled concrete, the phase change material absorbs heat through phase change, which can effectively reduce the temperature rise rate inside the large volume of concrete and prevent or prevent early thermal cracks caused by different heat dissipation conditions inside and outside the concrete during cement hydration. At present, phase change energy storage materials are easy to seep out during the freeze-thaw process, affecting the stability and service life of phase change insulation materials, which needs to be solved urgently. Summary of the invention
[0005] The purpose of the present invention is to solve the shortcomings of the prior art and to propose a phase change energy storage thermal insulation building material and a preparation method thereof.
[0006] A phase-change energy storage and heat-insulating building material, the raw materials of which include, by mass, 80-150 parts of cement, 40-70 parts of fly ash, 5-12 parts of polypropylene fiber, 1-3 parts of water reducer, 1-2 parts of polyethylene glycol diglycidyl ether, 0.25-0.6 parts of hydrogen peroxide, 5-10 parts of tetraethyl orthosilicate, 1-2 parts of polyvinyl pyrrolidone, 0.01-0.1 parts of silane coupling agent, 1-2 parts of carboxyl-terminated polyamidoamine, 0.01-0.1 parts of triethanolamine, 30-60 parts of paraffin, 1-5 parts of sodium oleate, 0.1-0.45 parts of calcium chloride and 0.025-0.144 parts of sodium dihydrogen phosphate.
[0007] Preferably, the silane coupling agent is silane coupling agent KH560.
[0008] Preferably, the generation number of the carboxyl-terminated polyamidoamine is 2.0-4.0 generations.
[0009] The preparation method of the above-mentioned phase change energy storage thermal insulation building material comprises the following steps:
[0010] S1. Add tetraethyl orthosilicate to ethanol aqueous solution and stir for 10-30 min, adjust the pH value of the system to 4-5, perform ultrasonic treatment for 1-2 h, add polyvinyl pyrrolidone, perform heat treatment at 50-70° C. for 1-2 h, cool to room temperature, adjust the pH value of the system to 8-9, perform ultrasonic treatment for 1-2 h, centrifuge, wash, and calcine at 180-220° C. for 10-30 min to obtain porous silica;
[0011] S2, adding porous silica and silane coupling agent to ethanol aqueous solution, stirring at 40-50° C. for 1-2 hours, adjusting the pH value of the system to 8-9, adding carboxyl-terminated polyamidoamine and triethanolamine, reacting at 70-80° C. for 5-10 hours, filtering, washing, and vacuum drying to obtain activated silica;
[0012] S3, heating the paraffin to a molten state, adding activated silicon dioxide and ultrasonically treating for 1-2 hours, and vacuum adsorption treatment to obtain a phase change material;
[0013] S4, adding sodium oleate to water, stirring evenly at 90-95°C, adding calcium chloride aqueous solution and sodium dihydrogen phosphate aqueous solution in sequence under stirring, adding phase change material thereto, cooling to room temperature, standing for 1-5h, filtering, washing, and vacuum drying to obtain a loaded phase change material;
[0014] S5. Stir cement, fly ash, polypropylene fiber, water reducing agent and polyethylene glycol diglycidyl ether for 1-2 minutes, add the loaded phase change material and stir for 1-2 minutes, add hydrogen peroxide and stir for 1-2 minutes, pour into the mold and shake slightly, seal and cure at 20-30℃ for 7-15 days.
[0015] Preferably, in S1, the mass fraction of the ethanol aqueous solution is 50-70%.
[0016] Preferably, in S1, after adjusting the pH value of the system to 4-5, the ultrasonic frequency of the ultrasonic treatment is 5-12 kHz.
[0017] Preferably, in S1, after adjusting the pH value of the system to 8-9, the ultrasonic frequency of the ultrasonic treatment is 5-12 kHz.
[0018] Preferably, in S3, the ultrasonic frequency is 5-12 kHz.
[0019] Preferably, in S4, the mass fraction of the calcium chloride aqueous solution is 1-1.5%, and the mass fraction of the sodium dihydrogen phosphate aqueous solution is 0.5-1.2%.
[0020] Preferably, in S3, the mass fraction of hydrogen peroxide is 25-30%.
[0021] Beneficial effects:
[0022] The invention adopts tetraethyl orthosilicate and polyvinyl pyrrolidone to form porous silica through calcination, and completely absorbs paraffin into the pores of the porous silica through vacuum adsorption. The paraffin has excellent dispersion performance in the porous silica and is not easy to overflow in the subsequent loading process, and has extremely high bonding stability. The paraffin is combined with polyethylene glycol diglycidyl ether to be more firmly bonded in the form of chemical bonds. The building material is mixed with cement, fly ash and polypropylene fiber to prepare the building material. It is found through experiments that the invention can maintain working stability at a relatively high temperature and still has good working stability after a long period of freeze-thaw cycles.
[0023] The present invention deposits nanowires on the surface of the phase change material and overlaps them to form a network structure. The dendritic polyamide amine can effectively fix the paraffin, effectively disperse and transfer stress, and effectively enhance the strength of the material. By controlling the ratio of the loaded phase change material to cement, the material can have excellent antifreeze performance and greatly enhanced stability in use while ensuring its tensile strength.
[0024] The present invention forms a porous matrix structure by compounding the loaded phase change material with hydrogen peroxide, and the material has good thermal insulation and heat storage performance, and the phase change heat storage performance is stable and green and environmentally friendly.
[0025] The loaded phase change material obtained by the present invention has a large loading rate for paraffin, good anti-leakage performance, and the characteristics of thermal energy storage and release, and can be applied to latent heat storage and release. At the same time, the preparation process is simple and easy to control, green and environmentally friendly, and has excellent application prospects in the field of energy-saving buildings. BRIEF DESCRIPTION OF THE DRAWINGS
[0026] Figure 1It is a comparison chart of the compressive strength and splitting tensile strength of the phase change energy storage thermal insulation building materials obtained in Example 5 and Comparative Examples 1-2.
[0027] Figure 2 This is a comparison chart of the mass loss rate of the phase change energy storage thermal insulation building materials obtained in Example 5 and Comparative Examples 1-2 after freeze-thaw cycles.
[0028] Figure 3 This is a comparison chart of the compressive strength retention rate of the phase change energy storage thermal insulation building materials obtained in Example 5 and Comparative Examples 1-2 after freeze-thaw cycles. DETAILED DESCRIPTION
[0029] The present invention will be further explained below in conjunction with specific embodiments.
[0030] Example 1
[0031] A phase-change energy storage and heat-insulating building material, whose raw materials include: 800g of cement, 400g of fly ash, 50g of polypropylene fiber, 10g of water reducing agent, 10g of polyethylene glycol diglycidyl ether, 2.5g of hydrogen peroxide, 50g of tetraethyl orthosilicate, 10g of polyvinyl pyrrolidone, 0.1g of coupling agent KH5600, 10g of 2.0-generation carboxyl-terminated polyamidoamine, 0.1g of triethanolamine, 300g of paraffin, 10g of sodium oleate, 1g of calcium chloride, and 0.25g of sodium dihydrogen phosphate.
[0032] The preparation method of the above-mentioned phase change energy storage thermal insulation building material comprises the following steps:
[0033] S1. Add ethyl orthosilicate to 400g of 50% ethanol aqueous solution, stir at 100r / min for 10min, adjust the pH value of the system to 4-5 with 0.5mol / L acetic acid solution, perform ultrasonic treatment for 1h at an ultrasonic frequency of 5kHz, add polyvinyl pyrrolidone, perform heat treatment at 50°C for 1h, cool to room temperature, add ammonia water to adjust the pH value of the system to 8-9, perform ultrasonic treatment for 1h at an ultrasonic frequency of 5kHz, centrifuge, wash, and calcine at 180°C for 10min to obtain porous silica;
[0034] S2, adding porous silica and coupling agent KH560 to 500g of 50% ethanol aqueous solution, stirring at 40°C for 1h, adjusting the pH value of the system to 8-9, adding carboxyl-terminated polyamidoamine and triethanolamine, reacting at 70°C for 5h, filtering, washing, and vacuum drying to obtain activated silica;
[0035] S3, heat the paraffin to a molten state, add activated silicon dioxide and ultrasonically treat for 1 hour, the ultrasonic frequency is 5kHz, send it into a vacuum adsorption tank, and repeatedly adsorb it twice in a vacuum state to obtain a phase change material;
[0036] S4, adding sodium oleate to 600g of water, stirring evenly at a temperature of 90°C, adding 1% by mass calcium chloride aqueous solution and 0.5% by mass sodium dihydrogen phosphate aqueous solution thereto in sequence under stirring, stirring at a speed of 1000r / min, adding phase change material thereto, cooling to room temperature, standing for 1h, filtering, washing, and vacuum drying to obtain a loaded phase change material;
[0037] S5. Stir cement, fly ash, polypropylene fiber, water reducing agent and polyethylene glycol diglycidyl ether for 1 min, add loaded phase change material and stir at a speed of 500 r / min for 1 min, add 25% hydrogen peroxide and stir for 1 min, pour into a mold and shake slightly, send to a constant temperature chamber and seal for curing for 7 days at a curing temperature of 20°C.
[0038] Example 2
[0039] A phase-change energy storage and heat-insulating building material, whose raw materials include: 1500g of cement, 700g of fly ash, 120g of polypropylene fiber, 30g of water reducer, 20g of polyethylene glycol diglycidyl ether, 6g of hydrogen peroxide, 100g of tetraethyl orthosilicate, 20g of polyvinyl pyrrolidone, 1g of coupling agent KH560, 20g of 4.0-generation carboxyl-terminated polyamidoamine, 1g of triethanolamine, 600g of paraffin, 50g of sodium oleate, 4.5g of calcium chloride, and 1.44g of sodium dihydrogen phosphate.
[0040] The preparation method of the above-mentioned phase change energy storage thermal insulation building material comprises the following steps:
[0041] S1. Add ethyl orthosilicate to 800g of 70% ethanol aqueous solution, stir at 500r / min for 30min, adjust the pH value of the system to 4-5 with 1.2mol / L acetic acid solution, ultrasonically treat for 2h at a frequency of 12kHz, add polyvinyl pyrrolidone, heat treat at 70°C for 2h, cool to room temperature, add ammonia water to adjust the pH value of the system to 8-9, ultrasonically treat for 2h at a frequency of 12kHz, centrifuge, wash, and calcine at 220°C for 30min to obtain porous silica;
[0042] S2, adding porous silica and coupling agent KH560 to 1000g of 70% ethanol aqueous solution, stirring at 50°C for 2h, adjusting the pH value of the system to 8-9, adding carboxyl-terminated polyamidoamine and triethanolamine, reacting at 80°C for 10h, filtering, washing, and vacuum drying to obtain activated silica;
[0043] S3, heat the paraffin to a molten state, add activated silicon dioxide and ultrasonically treat for 2 hours, the ultrasonic frequency is 12kHz, send it into a vacuum adsorption tank, and repeatedly adsorb it in a vacuum state for 4 times to obtain a phase change material;
[0044] S4, adding sodium oleate to 1000g water, stirring evenly at a temperature of 95°C, adding a 1.5% by mass calcium chloride aqueous solution and a 1.2% by mass sodium dihydrogen phosphate aqueous solution thereto in sequence under stirring, stirring at a speed of 2000r / min, adding a phase change material thereto, cooling to room temperature, standing for 5h, filtering, washing, and vacuum drying to obtain a loaded phase change material;
[0045] S5. Stir cement, fly ash, polypropylene fiber, water reducing agent and polyethylene glycol diglycidyl ether for 2 minutes, add loaded phase change material, stir at a speed of 1000r / min for 2 minutes, add 30% hydrogen peroxide and stir for 2 minutes, pour into a mold and shake slightly, send to a constant temperature chamber and seal for curing for 15 days at a curing temperature of 30°C.
[0046] Example 3
[0047] A phase-change energy storage and heat-insulating building material, whose raw materials include: 1000g of cement, 600g of fly ash, 60g of polypropylene fiber, 25g of water reducer, 13g of polyethylene glycol diglycidyl ether, 5g of hydrogen peroxide, 70g of tetraethyl orthosilicate, 18g of polyvinyl pyrrolidone, 0.3g of coupling agent KH560, 18g of 3.0-generation carboxyl-terminated polyamidoamine, 0.3g of triethanolamine, 500g of paraffin, 20g of sodium oleate, 4g of calcium chloride, and 0.4g of sodium dihydrogen phosphate.
[0048] The preparation method of the above-mentioned phase change energy storage thermal insulation building material comprises the following steps:
[0049] S1. Add ethyl orthosilicate to 700g of 55% ethanol aqueous solution, stir at 400r / min for 15min, adjust the pH value of the system to 4-5 with 1mol / L acetic acid solution, ultrasonically treat for 80min at an ultrasonic frequency of 10kHz, add polyvinyl pyrrolidone, heat treat at 55°C for 100min, cool to room temperature, add ammonia water to adjust the pH value of the system to 8-9, ultrasonically treat for 80min at an ultrasonic frequency of 10kHz, centrifuge, wash, and calcine at 190°C for 25min to obtain porous silica;
[0050] S2, adding porous silica and coupling agent KH560 to 600g of 65% ethanol aqueous solution, stirring at 43°C for 100min, adjusting the pH value of the system to 8-9, adding carboxyl-terminated polyamidoamine and triethanolamine, reacting at 73°C for 9h, filtering, washing, and vacuum drying to obtain activated silica;
[0051] S3, heat the paraffin to a molten state, add activated silicon dioxide and ultrasonically treat for 80 minutes at an ultrasonic frequency of 10 kHz, send it into a vacuum adsorption tank, and repeatedly adsorb it three times in a vacuum state to obtain a phase change material;
[0052] S4, adding sodium oleate to 700g of water, stirring evenly at a temperature of 94°C, adding a 1.1% by mass calcium chloride aqueous solution and a 1% by mass sodium dihydrogen phosphate aqueous solution thereto in sequence under stirring, stirring at a speed of 1200r / min, adding a phase change material thereto, cooling to room temperature, standing for 4h, filtering, washing, and vacuum drying to obtain a loaded phase change material;
[0053] S5. Stir cement, fly ash, polypropylene fiber, water reducing agent and polyethylene glycol diglycidyl ether for 1.5 minutes, add loaded phase change material, stir at a speed of 600r / min for 1.5 minutes, add 29% hydrogen peroxide and stir for 1.5 minutes, pour into a mold and shake slightly, send to a constant temperature chamber and seal for curing for 9 days at a curing temperature of 28°C.
[0054] Example 4
[0055] A phase-change energy storage and heat-insulating building material, whose raw materials include: 1300g of cement, 500g of fly ash, 100g of polypropylene fiber, 15g of water reducing agent, 17g of polyethylene glycol diglycidyl ether, 4g of hydrogen peroxide, 90g of tetraethyl orthosilicate, 12g of polyvinyl pyrrolidone, 0.7g of coupling agent KH560, 12g of 3.0-generation carboxyl-terminated polyamidoamine, 0.7g of triethanolamine, 400g of paraffin, 40g of sodium oleate, 2g of calcium chloride and 1.2g of sodium dihydrogen phosphate.
[0056] The preparation method of the above-mentioned phase change energy storage thermal insulation building material comprises the following steps:
[0057] S1. Add ethyl orthosilicate to 500 g of 65% ethanol aqueous solution, stir at 200 r / min for 25 min, adjust the pH value of the system to 4-5 with 0.6 mol / L acetic acid solution, perform ultrasonic treatment for 100 min at a frequency of 6 kHz, add polyvinyl pyrrolidone, perform heat treatment at 65°C for 80 min, cool to room temperature, add ammonia water to adjust the pH value of the system to 8-9, perform ultrasonic treatment for 100 min at a frequency of 6 kHz, centrifuge, wash, and calcine at 210°C for 15 min to obtain porous silica;
[0058] S2, adding porous silica and coupling agent KH560 to 900g of 55% ethanol aqueous solution, stirring at 47°C for 80min, adjusting the pH value of the system to 8-9, adding carboxyl-terminated polyamidoamine and triethanolamine, reacting at 77°C for 6h, filtering, washing, and vacuum drying to obtain activated silica;
[0059] S3, heat the paraffin to a molten state, add activated silicon dioxide and ultrasonically treat for 100 min at an ultrasonic frequency of 6 kHz, send it into a vacuum adsorption tank, and repeatedly adsorb it in a vacuum state for 3 times to obtain a phase change material;
[0060] S4, adding sodium oleate to 900g of water, stirring evenly at a temperature of 92°C, adding a 1.3% by mass calcium chloride aqueous solution and a 0.6% by mass sodium dihydrogen phosphate aqueous solution thereto in sequence under stirring, stirring at a speed of 1800r / min, adding a phase change material thereto, cooling to room temperature, standing for 2h, filtering, washing, and vacuum drying to obtain a loaded phase change material;
[0061] S5. Stir cement, fly ash, polypropylene fiber, water reducing agent and polyethylene glycol diglycidyl ether for 1.5 minutes, add loaded phase change material, stir at a speed of 800r / min for 1.5 minutes, add 27% hydrogen peroxide and stir for 1.5 minutes, pour into a mold and shake slightly, send to a constant temperature chamber and seal for curing for 12 days at a curing temperature of 22°C.
[0062] Example 5
[0063] A phase-change energy storage and heat-insulating building material, whose raw materials include: 1200g of cement, 550g of fly ash, 80g of polypropylene fiber, 20g of water reducer, 15g of polyethylene glycol diglycidyl ether, 4.5g of hydrogen peroxide, 80g of tetraethyl orthosilicate, 15g of polyvinyl pyrrolidone, 0.5g of coupling agent KH560, 15g of 3.0-generation carboxyl-terminated polyamidoamine, 0.5g of triethanolamine, 450g of paraffin, 30g of sodium oleate, 3g of calcium chloride, and 0.8g of sodium dihydrogen phosphate.
[0064] The preparation method of the above-mentioned phase change energy storage thermal insulation building material comprises the following steps:
[0065] S1. Add ethyl orthosilicate to 600 g of 60% ethanol aqueous solution, stir at 300 r / min for 20 min, adjust the pH value of the system to 4-5 with 0.8 mol / L acetic acid solution, perform ultrasonic treatment for 90 min at an ultrasonic frequency of 9 kHz, add polyvinyl pyrrolidone, perform heat treatment at 60°C for 90 min, cool to room temperature, add ammonia water to adjust the pH value of the system to 8-9, perform ultrasonic treatment for 90 min at an ultrasonic frequency of 9 kHz, centrifuge, wash, and calcine at 200°C for 20 min to obtain porous silica;
[0066] S2, adding porous silica and coupling agent KH560 to 750g of 60% ethanol aqueous solution, stirring at 45°C for 90min, adjusting the pH value of the system to 8-9, adding carboxyl-terminated polyamidoamine and triethanolamine, reacting at 75°C for 8h, filtering, washing, and vacuum drying to obtain activated silica;
[0067] S3, heat the paraffin to a molten state, add activated silicon dioxide and ultrasonically treat for 90 minutes at an ultrasonic frequency of 9 kHz, send it into a vacuum adsorption tank, and repeatedly adsorb it three times in a vacuum state to obtain a phase change material;
[0068] S4, adding sodium oleate to 800g of water, stirring evenly at a temperature of 93°C, adding a 1.2% by mass calcium chloride aqueous solution and a 0.8% by mass sodium dihydrogen phosphate aqueous solution thereto in sequence under stirring, stirring at a speed of 1500r / min, adding a phase change material thereto, cooling to room temperature, standing for 3h, filtering, washing, and vacuum drying to obtain a loaded phase change material;
[0069] S5. Stir cement, fly ash, polypropylene fiber, water reducing agent and polyethylene glycol diglycidyl ether for 1.5 minutes, add loaded phase change material, stir at 700r / min for 1.5 minutes, add 28% hydrogen peroxide and stir for 1.5 minutes, pour into a mold and shake slightly, send to a constant temperature chamber and seal for curing for 10 days at a curing temperature of 25°C.
[0070] Comparative Example 1
[0071] A phase-change energy storage and heat-insulating building material, whose raw materials include: 1200g of cement, 550g of fly ash, 80g of polypropylene fiber, 20g of water reducer, 15g of polyethylene glycol diglycidyl ether, 4.5g of hydrogen peroxide, 80g of tetraethyl orthosilicate, 15g of polyvinyl pyrrolidone, 0.5g of coupling agent KH560, 15g of 3.0-generation carboxyl-terminated polyamidoamine, 0.5g of triethanolamine, 450g of paraffin, 30g of sodium oleate, 3g of calcium chloride, and 0.8g of sodium dihydrogen phosphate.
[0072] The preparation method of the above-mentioned phase change energy storage thermal insulation building material comprises the following steps:
[0073] S1. Add ethyl orthosilicate to 600 g of 60% ethanol aqueous solution, stir at 300 r / min for 20 min, adjust the pH value of the system to 4-5 with 0.8 mol / L acetic acid solution, perform ultrasonic treatment for 90 min at an ultrasonic frequency of 9 kHz, add polyvinyl pyrrolidone, perform heat treatment at 60°C for 90 min, cool to room temperature, add ammonia water to adjust the pH value of the system to 8-9, perform ultrasonic treatment for 90 min at an ultrasonic frequency of 9 kHz, centrifuge, wash, and calcine at 200°C for 20 min to obtain porous silica;
[0074] S2, heat the paraffin to a molten state, add porous silica and ultrasonically treat for 90 minutes at an ultrasonic frequency of 9 kHz, send it into a vacuum adsorption tank, and repeatedly adsorb it three times in a vacuum state to obtain a phase change material;
[0075] S3, adding sodium oleate to 800g of water, stirring evenly at a temperature of 93°C, adding a 1.2% by mass calcium chloride aqueous solution and a 0.8% by mass sodium dihydrogen phosphate aqueous solution thereto in sequence under stirring, stirring at a speed of 1500r / min, adding a phase change material thereto, cooling to room temperature, standing for 3h, filtering, washing, and vacuum drying to obtain a loaded phase change material;
[0076] S4. Stir cement, fly ash, polypropylene fiber, water reducing agent and polyethylene glycol diglycidyl ether for 1.5 minutes, add carboxyl-terminated polyamide amine and loaded phase change material, stir at 700r / min for 1.5 minutes, add 28% hydrogen peroxide and stir for 1.5 minutes, pour into a mold and shake slightly, send to a constant temperature chamber and seal for curing for 10 days at a curing temperature of 25°C.
[0077] Comparative Example 2
[0078] A phase-change energy storage and heat-insulating building material, whose raw materials include: 1200g of cement, 550g of fly ash, 80g of polypropylene fiber, 20g of water reducer, 15g of polyethylene glycol diglycidyl ether, 4.5g of hydrogen peroxide, 80g of tetraethyl orthosilicate, 15g of polyvinyl pyrrolidone, 0.5g of coupling agent KH560, 15g of 3.0-generation carboxyl-terminated polyamidoamine, 0.5g of triethanolamine, 450g of paraffin, 30g of sodium oleate, 3g of calcium chloride, and 0.8g of sodium dihydrogen phosphate.
[0079] The preparation method of the above-mentioned phase change energy storage thermal insulation building material comprises the following steps:
[0080] S1. Add ethyl orthosilicate to 600 g of 60% ethanol aqueous solution, stir at 300 r / min for 20 min, adjust the pH value of the system to 4-5 with 0.8 mol / L acetic acid solution, perform ultrasonic treatment for 90 min at an ultrasonic frequency of 9 kHz, add polyvinyl pyrrolidone, perform heat treatment at 60°C for 90 min, cool to room temperature, add ammonia water to adjust the pH value of the system to 8-9, perform ultrasonic treatment for 90 min at an ultrasonic frequency of 9 kHz, centrifuge, wash, and calcine at 200°C for 20 min to obtain porous silica;
[0081] S2, adding porous silica and coupling agent KH560 to 750g of 60% ethanol aqueous solution, stirring at 45°C for 90min, adjusting the pH value of the system to 8-9, adding carboxyl-terminated polyamidoamine and triethanolamine, reacting at 75°C for 8h, filtering, washing, and vacuum drying to obtain activated silica;
[0082] S3, heat the paraffin to a molten state, add activated silicon dioxide and ultrasonically treat for 90 minutes at an ultrasonic frequency of 9 kHz, send it into a vacuum adsorption tank, and repeatedly adsorb it three times in a vacuum state to obtain a phase change material;
[0083] S4, adding sodium oleate to 800g of water, stirring at a temperature of 93°C, adding a 1.2% by mass fraction of calcium chloride aqueous solution and a 0.8% by mass fraction of sodium dihydrogen phosphate aqueous solution thereto in sequence under stirring, stirring at a speed of 1500r / min, cooling to room temperature, standing for 3h, filtering, washing, and vacuum drying to obtain a loaded material;
[0084] S5. Stir cement, fly ash, polypropylene fiber, water reducing agent and polyethylene glycol diglycidyl ether for 1.5 minutes, add phase change material and load material, stir at 700r / min for 1.5 minutes, add 28% hydrogen peroxide and stir for 1.5 minutes, pour into a mold and shake slightly, send to a constant temperature chamber and seal for curing for 10 days at a curing temperature of 25°C.
[0085] With reference to GB / T 50081-2019 "Standard for Test Methods for Physical and Mechanical Properties of Concrete", the compressive properties of the phase change energy storage and thermal insulation building materials obtained in Example 5 and Comparative Examples 1-2 were measured using a rock compression elastic modulus tester.
[0086] With reference to SL / T 352-2020 "Test Procedures for Hydraulic Concrete", an electronic universal testing machine was used to measure the splitting tensile strength of the phase change energy storage and thermal insulation building materials obtained in Example 5 and Comparative Examples 1-2.
[0087] like Figure 1As shown, the compressive strength and splitting tensile strength of the phase change energy storage thermal insulation building material obtained in Example 5 are both the highest, which are better than those of Comparative Examples 1-2 (P < 0.05).
[0088] With reference to GB / T 50082-2009 "Standard for Test Methods for Long-term Performance and Durability of Ordinary Concrete", freeze-thaw cycle tests were carried out on the phase change energy storage thermal insulation building materials obtained in Example 5 and Comparative Examples 1-2 using a concrete rapid freeze-thaw tester.
[0089] The mass of the samples after experiencing different numbers of freeze-thaw cycles was measured, and the mass loss rate was calculated (when the mass loss rate reached 5%, it was considered as failure, and the freeze-thaw cycle of this group of samples was stopped); and the compressive strength of the samples after experiencing different numbers of freeze-thaw cycles was measured, and the compressive strength retention rate was calculated.
[0090] Mass loss rate = (1-mass of sample after freeze-thaw cycle ÷ mass of sample before freeze-thaw cycle) × 100%
[0091] Compressive strength retention rate = compressive strength of the sample after freeze-thaw cycle ÷ compressive strength of the sample before freeze-thaw cycle × 100%
[0092] like Figure 2 and Figure 3 As shown, the mass loss rate of the phase change energy storage thermal insulation building material obtained in Example 5 is always lower than that in Comparative Examples 1-2 (P < 0.05), while the compressive strength retention rate is always higher than that in Comparative Examples 1-2 (P < 0.05), confirming that the phase change energy storage thermal insulation building material obtained in Example 5 has the best anti-freeze-thaw performance.
[0093] The applicant believes that the reason for the above results is that the present invention uses tetraethyl orthosilicate and polyvinyl pyrrolidone to form porous silica after calcination, and uses vacuum adsorption to completely adsorb paraffin into the pores of porous silica, and cooperates with the grafted dendritic polyamide amine to make the paraffin have excellent dispersion performance therein, and it is not easy to overflow in the subsequent loading process, and the binding stability is extremely high. It is combined with polyethylene glycol diglycidyl ether, and the combination is more firmly in the form of chemical bonds, and is mixed with cement, fly ash, and polypropylene fiber to prepare building materials. The present invention further deposits nanowires on the surface of the phase change material and overlaps with each other to form a mesh structure. The dendritic polyamide amine can effectively fix the paraffin, effectively disperse and transfer stress, and effectively enhance the strength of the material. By controlling the ratio of the loaded phase change material to cement, the antifreeze performance is excellent on the basis of ensuring the tensile strength of the material, and the stability of use is greatly enhanced.
[0094] The above description is only a preferred specific implementation manner of the present invention, but the protection scope of the present invention is not limited thereto. Any technician familiar with the technical field can make equivalent replacements or changes according to the technical scheme and inventive concept of the present invention within the technical scope disclosed by the present invention, which should be covered by the protection scope of the present invention.
Claims
1. A phase change energy storage thermal insulation building material, characterized in that: The raw materials include, by mass, 80-150 parts of cement, 40-70 parts of fly ash, 5-12 parts of polypropylene fiber, 1-3 parts of water reducing agent, 1-2 parts of polyethylene glycol diglycidyl ether, 0.25-0.6 parts of hydrogen peroxide, 5-10 parts of tetraethyl orthosilicate, 1-2 parts of polyvinyl pyrrolidone, 0.01-0.1 parts of silane coupling agent, 1-2 parts of carboxyl-terminated polyamidoamine, 0.01-0.1 parts of triethanolamine, 30-60 parts of paraffin, 1-5 parts of sodium oleate, 0.1-0.45 parts of calcium chloride and 0.025-0.144 parts of sodium dihydrogen phosphate.
2. The phase change energy storage thermal insulation building material according to claim 1, characterized in that: The silane coupling agent is silane coupling agent KH560.
3. The phase change energy storage thermal insulation building material according to claim 1, characterized in that: The generation number of the carboxyl-terminated polyamidoamine is 2.0-4.0 generations.
4. A method for preparing the phase-change energy storage thermal insulation building material according to any one of claims 1 to 3, characterized in that: The steps include: S1. Add tetraethyl orthosilicate to ethanol aqueous solution and stir for 10-30 min, adjust the pH value of the system to 4-5, perform ultrasonic treatment for 1-2 h, add polyvinyl pyrrolidone, perform heat treatment at 50-70° C. for 1-2 h, cool to room temperature, adjust the pH value of the system to 8-9, perform ultrasonic treatment for 1-2 h, centrifuge, wash, and calcine at 180-220° C. for 10-30 min to obtain porous silica; S2, adding porous silica and silane coupling agent to ethanol aqueous solution, stirring at 40-50° C. for 1-2 hours, adjusting the pH value of the system to 8-9, adding carboxyl-terminated polyamidoamine and triethanolamine, reacting at 70-80° C. for 5-10 hours, filtering, washing, and vacuum drying to obtain activated silica; S3, heating the paraffin to a molten state, adding activated silicon dioxide and ultrasonically treating for 1-2 hours, and vacuum adsorption treatment to obtain a phase change material; S4, adding sodium oleate to water, stirring evenly at 90-95°C, adding calcium chloride aqueous solution and sodium dihydrogen phosphate aqueous solution in sequence under stirring, adding phase change material thereto, cooling to room temperature, standing for 1-5h, filtering, washing, and vacuum drying to obtain a loaded phase change material; S5. Stir cement, fly ash, polypropylene fiber, water reducing agent and polyethylene glycol diglycidyl ether for 1-2 minutes, add the loaded phase change material and stir for 1-2 minutes, add hydrogen peroxide and stir for 1-2 minutes, pour into the mold and shake slightly, seal and cure at 20-30℃ for 7-15 days.
5. The method for preparing the phase-change energy storage thermal insulation building material according to claim 4, characterized in that: In S1, the mass fraction of the ethanol aqueous solution is 50-70%.
6. The method for preparing the phase-change energy storage thermal insulation building material according to claim 4, characterized in that: In S1, the pH value of the system is adjusted to 4-5 and the ultrasonic frequency of the ultrasonic treatment is 5-12 kHz.
7. The method for preparing the phase-change energy storage thermal insulation building material according to claim 4, characterized in that: In S1, the pH value of the system is adjusted to 8-9 and then the ultrasonic treatment is performed at an ultrasonic frequency of 5-12 kHz.
8. The method for preparing the phase-change energy storage thermal insulation building material according to claim 4, characterized in that: In S3, the ultrasound frequency is 5-12kHz.
9. The method for preparing the phase-change energy storage thermal insulation building material according to claim 4, characterized in that: In S4, the mass fraction of the calcium chloride aqueous solution is 1-1.5%, and the mass fraction of the sodium dihydrogen phosphate aqueous solution is 0.5-1.2%.
10. The method for preparing the phase-change energy storage thermal insulation building material according to claim 4, characterized in that: In S3, the mass fraction of hydrogen peroxide is 25-30%.
Citation Information
Patent Citations
Self-emulsifying epoxy group composite material which is heat conducting and waterproof, and preparation method and application of composite material
CN104559067A
Phase-change energy storage building thermal insulation material and preparation method thereof
CN106928905A
Preparation method of flexible silicon dioxide aerogel based phase change composite
CN107523275A
Inorganic composite diatom mud coating material
CN108191378A
Heat storage material with high and low two-phase transition temperature and preparation method thereof
CN119060522A